IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DAN KURIKULUM 2013 DALAM MENINGKATKAN MUTU PEMBELAJARAN AGAMA ISLAM DI SMP MADINATUL HADID CILEGON DAN SMP NEGERI 1 CILEGON - Muhajir Muhajir; Zaenal Muttaqin (QATHRUNÂ, 2018)
In order to respond to various changes in efforts required to improve the relevance and quality of education, one of the concrete results of the hard work effort is the formulation of the curriculum as an effort to improve the quality of education and learning process. Curriculum changes are expected to improve the quality of education. Implementation of any curriculum in learning, the attainment of a quality educational process becomes the most important part. Curriculum as a basic benchmark or reference of teachers in implementing and developing learning in which there are standards to be achieved so that the results of the implementation of the curriculum can achieve the goal of national education maximally. This study aims to know the implementation of Education Unit Level Curriculum (KTSP) 2006 in Madinatul Hadid Cilegon Junior High School and the implementation of Curriculum 2013 in SMP Negeri 1 Cilegon. Knowing the quality of learning Islamic Religious Education in Madinatul Hadid Cilegon Junior High School and in SMP Negeri 1 Cilegon. Knowing the indicators of successful implementation of Education Unit Level Curriculum (KTSP) 2006 at SMP Madinatul Hadid Cilegon and Curriculum 2013 at SMP Negeri 1 Cilegon. Knowing the implementation analysis of Education Unit Level Curriculum (KTSP) 2006 in Madinatul Hadid Cilegon Junior High School and Curriculum 2013 at SMP Negeri 1 Cilegon. Knowing the factors driving and impeding the implementation of Education Unit Level Curriculum (KTSP) 2006 in Madinatul Hadid Cilegon Junior High School and in SMP Negeri 1 Cilegon. The results of this study concluded that: (1) Implementation Curriculum in Madinatul Hadid Cilegon junior, using active learning, creative, and fun. Implementation Curriculum in SMP Negeri 1 Cilegon, using scientific pendektan / scientific. (2) The quality of PAI learning at SMP Madinatul Hadid Cilegon, and SMP Negeri 1 Cilegon, can be seen from the result of USBN PAI in Madinatul Hadid junior high school with an average score of 76.16, the highest score of 86 and the lowest score of 58 and the 88% completeness rate. While the results of USBN PAI in SMP N 1 Cilegon, the average value is 89.14, the highest value 98 and the lowest score 82 and 100% completeness level (3) The successful implementation of the Curriculum at Madinatul Hadid Cilegon Junior High School, the independence and initiative of principals and teachers in managing and utilizing available resources. Learning is successful when ≥ 75% of learners are actively involved in learning. Successful implementation of curriculum in SMP Negeri 1 Cilegon, can be seen the improvement of the relationship between school personnel and society. Learning is considered complete if students are able to complete and master the ability ≥ 80%. (4) Implementation of Curriculum at Madinatul Hadid Cilegon Junior High School, in accordance with Competency Standards and Basic Competency, with 2x40 minute face-to-face hours. Implementation Curriculum in SMP Negeri 1 Cilegon, according to SKL in it there is implementation of KI-KD with hours per week 3x40 minutes. (5) Madinatul Hadid Cilegon Management Curriculum, improving learning strategy with benchmark of student achievement. Management of Krikulum at SMP Negeri 1 Cilegon through School-Based Quality Improvement Management (MPMBS)